Edward O. Wolcott, The Ordinances of Georgetown, Passed June 7th, A.D. 1877, at 100, § 9 (1877) - (:unkn) unknown (My University, 1877)
Prohibited the concealed carrying of any pistol, Bowie knife, dagger, or other deadly weapon. Punishable by a fine of $5-50.
Keywords: CARRY - CONCEALED